Reduction of Negative Effects For Moisture Tention of the Corn Plant by Spraying with Proline acid and Abscisic Acid. - Mohammed, Hussein A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This experiment was conducted in field of Agricultured Department Baquba/Diyala province in spring season 2011 to study the water stress by using foliar application concentrations of each Proline acid and Abscisic acid on proline content , ABA content , chlorophyll content, protein conten and water content in leaves of Maize( cultivar, Buhooth 106). The layout of the experiments was Split- split plot design as RCBD with three replicates. The three concentrations of spraying Proline acid levels ( 0 , 150 , 200 mg Proline .l-1 ) Three Abscisic acid levels ( 0 , 15 , 20 mgABA.l-1. ) and three periods of irrigation after(25, 50, 75%) of available water . Folair fertilizer were applied at three time during of plant growth. Results drawn from these experiments are summarized as follows: The therd level of Proline acid sprayed 200 mg Proline .l-1 ) decreased the negative effects of moisture tension on proline content , chlorophyll content, protein conten and water content in leaves as compared with the both of control and the second level (150 mg Proline.l-1. ) . The therd level of Proline acid sprayed ( 20 mgABA.l-1.) decreased the negative effects of moisture tension on proline content, ABA content and water content in leaves as compared with the control . Also the most of characters were significantly influenced by interaction between moisture levels x Proline acid and Abscisic acid concentrations.